PENGARUH KUALITAS PELAYANAN, RELATIONSHIP MARKETING DAN CORPORATE SOCIAL RESPOSIBILITY TERHADAP LOYALITAS DAN KEPUASAN NASABAH BANK - Yunita Kurnia Sari (Magister Manajemen Fakultas Ekonomi dan Bisnis UNS, 2017)
This study aims to provide empirical evidence about the influence of Quality of Service, Relationship Marketing, Corporate Social Responsibility and customer satisfaction to customer loyalty in BRI branch Tebing Tinggi. By using the 150 respondents BRI customers Tebing Tinggi branch determination technique in 2016. Convenience sampling is sampling, that the sampling technique with a collection of information from members of the population that is easily available and able to provide such information. Mechanical testing of hypotheses using multiple regression analysis and path analysis.F test results showed that simultaneous all independent variables affect the customer loyalty. Based on t test results can be concluded that customer satisfaction has a significant positive effect on customer satisfaction and customer loyalty. Relationship Marketing is not a significant effect on customer satisfaction and loyalty, while CSR significant effect on loyalty but has no significant effect on customer satisfaction. Further significant variable customer satisfaction has a significant positive effect on customer loyalty.